2018
DOI: 10.1111/ajad.12738
|View full text |Cite
|
Sign up to set email alerts
|

Dual use of alcohol and marijuana and condomless sex in young adult men and women: A within‐subject day‐level analysis

Abstract: Young women may be especially susceptible to the influence of alcohol and/or marijuana use on sexual behavior. (Am J Addict 2018;XX:1-6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Similar to evidence that the effects of substance use on sexual behavior are potentiated when alcohol and cannabis are combined, [2][3][4] we found that combined use of these substances was associated with lower levels of internal consent feelings. Specifically, people felt relatively less safe/comfortable when both alcohol and cannabis were involved; they also rated these sexual events as less consensual.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to evidence that the effects of substance use on sexual behavior are potentiated when alcohol and cannabis are combined, [2][3][4] we found that combined use of these substances was associated with lower levels of internal consent feelings. Specifically, people felt relatively less safe/comfortable when both alcohol and cannabis were involved; they also rated these sexual events as less consensual.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the potentiating effects of combined use of alcohol and cannabis on subjective intoxication ratings 29 and on other aspects of sexual behavior, [2][3][4] we expected people's sexual consent during sexual events with combined use to differ from events that involved only one of these substances or neither. However, given the mixed and limited findings across studies on substance use and sexual consent, we approached these preliminary data in an exploratory manner and did not make directional hypotheses.…”
Section: Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…When combined with alcohol’s potential side effect of blackouts (Wetherill & Fromme, 2016), marijuana use may result in greater levels of cognitive impairment, putting individuals at increased risk for making more impulsive decisions. For example, studies using timeline follow-back (Hayaki, Anderson, & Stein, 2018; Metrik, Caswell, Magill, Monti, & Kahler, 2016), event-based (Egan et al, 2019), and daily diary (Parks, Collins, & Derrick, 2012) designs show that using both alcohol and marijuana on the same day synergistically increases the likelihood of unprotected sex on that day among young adults. Importantly, a study by Metrik and colleagues (2016) found this was true for heavy (5+/4+ drinks per occasion) but not moderate drinking.…”
Section: Sam Use and Adverse Outcomesmentioning
confidence: 99%